Formulation and Characterization of Herbal Lip Balm Utilizing Red Dragon Fruit (Hylocereus polyrhizus) Extract as a Natural Colorant and Active Ingredient - Samosir, Harrys; Sarmila, Tina; Maharani, Loza Asmi Nahara; Samosir, Devina Sanchia (Eksergi, 2026)
This study formulated an herbal lip balm using dragon fruit extract (Hylocereus spp.) as a natural colorant and moisturizer. The extract was integrated with a base of coconut oil, beeswax, cocoa butter, vitamin E, and rose water. Physical testing indicated an average pH of 5.08 and a melting point of 63–65 °C, complying with standard safety requirements for lip care products. Organoleptic evaluation by 10 panelists demonstrated high acceptance, with 90% approving the soft texture and aroma, and 85% favoring the natural pink color. The product exhibited stability over a 28-day storage period. Material characterization via X-Ray Diffraction (XRD) identified an amorphous crystal structure (2θ ≈ 25.60 ), while Scanning Electron Microscopy (SEM) revealed a porous surface with a particle distribution of 8μm. X-Ray Fluorescence (XRF) analysis confirmed the extract is rich in macro-elements, specifically Potassium (67.5%), Calcium (15.5%), Magnesium (8.5%), and Phosphorus (8.4%).